2021
DOI: 10.3897/folmed.63.e51944
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of Purple Okra (Abelmoschus esculentus) to Green Okra in Insulin Resistance and Pancreatic β Cell Improvement in Diabetic Rats

Abstract: Introduction: Antidiabetic medicinal plants are increasingly used in the treatment of diabetes as they are generally assumed to pro-duce minimal side effects. Okra is a quercetin-containing plant which can induce pancreas regeneration and has antidiabetic effect. There has been a lot of research that demonstrate that purple okra contains more quercetin than green okra. Aim: To demonstrate the advantages of purple okra over green okra on the diabetic markers improvement in diabetic rats. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…We found that okra treatment in pre-diabetic and T2D patients has beneficial effects on glycaemic control, as demonstrated by a significant reduction in the level of FBG. These findings are consistent with the results reported by previous researchers ( Khatun et al, 2011 ; Majd et al, 2018 ; Nguekouo et al, 2018 ; Husen et al, 2020 ; Uadia et al, 2020 ; Wu et al, 2020 ; Yan et al, 2020 ; Tyagita et al, 2021 ; Haque et al, 2022 ). One of the proposed mechanisms that okra targets in reducing FBG is the stimulation of hepatic glycogen synthesis and pancreatic islet regeneration, thus leading to increased insulin secretion and subsequent delay in the intestinal absorption of glucose.…”
Section: Discussionsupporting
confidence: 93%
“…We found that okra treatment in pre-diabetic and T2D patients has beneficial effects on glycaemic control, as demonstrated by a significant reduction in the level of FBG. These findings are consistent with the results reported by previous researchers ( Khatun et al, 2011 ; Majd et al, 2018 ; Nguekouo et al, 2018 ; Husen et al, 2020 ; Uadia et al, 2020 ; Wu et al, 2020 ; Yan et al, 2020 ; Tyagita et al, 2021 ; Haque et al, 2022 ). One of the proposed mechanisms that okra targets in reducing FBG is the stimulation of hepatic glycogen synthesis and pancreatic islet regeneration, thus leading to increased insulin secretion and subsequent delay in the intestinal absorption of glucose.…”
Section: Discussionsupporting
confidence: 93%
“…The positive control group using acarbose on day 14 can reduce blood glucose levels until the mice are no longer in the diabetes category (> 200 mg/dL) (Malole and Purnomo 1989). The administration of acarbose in diabetic patients has improved pancreatic-cell function (Tyagita et al 2021). Increased blood glucose levels increase insulin secretion to improve the function of the remaining pancreatic β-cells (Chen et al 2014).…”
Section: The Effect Of Administering Perennial Sonchus Arvensis Leaf ...mentioning
confidence: 99%
“…Quercetin works by inhibiting sucrase, intestinal maltase, and GLUT-2 to inhibit glucose absorption, resulting in a decrease in blood glucose (Tyagita et al, 2021). GLUT-2 plays a significant role in glucose homeostasis and is expressed in pancreatic and liver β cells.…”
Section: Resultsmentioning
confidence: 99%